Internet technology and regional financial fraud: Evidence from Broadband expansion in China - Qihang Xue; Huimin Wang; Jian Wei (Journal of Applied Economics, 2023)
Combined with data from the Broadband China pilots, panel data on financial fraud in prefecture-level cities from China Judgments Online are used to examine the impact of internet technology on financial fraud. We find that internet technology has significantly increased city financial fraud. The causal effect still exists after the model validity test, excluding the selection bias of Broadband China pilot cities and the reporting effect of the internet. Furthermore, the trust effect is an important mechanism, and heterogeneity analysis shows that internet technology has a more significant impact on the financial fraud committed by highly educated and young fraudsters and on high-tech-dependent financial fraud.
Keywords: 330; Broadband China; financial fraud; Internet technology; trust effect